Tricalcium phosphate and hydroxyapatite treatment for benign cavitary bone lesions: A prospective clinical trial - Dragosloveanu, Şerban (Exp Ther Med, 2020)
Benign bone tumors are surgically treated by curettage and by filling the defect using bone grafts or bone substitutes, such as hydroxyapatite crystals and tricalcium phosphate. The tricalcium phosphate mixed with hydroxyapatite, although fragile, is a good alternative with good integration. Fifteen patients with benign bone lesions were randomized in two groups surgically treated by curettage and filling of the bone defect using allograft (7 cases) or a mixture of 35% tricalcium phosphate, with 60-85% pore volume, and 65% hydroxyapatite (8 cases). After the surgery, all patients were followed up every 3 weeks until 6 months, and then at 2 months interval until one year for the clinical and radiological assessment. The average age was 35.4 years (from 18 to 54) for the allograft group and 41 years (from 22 to 58) for the patients treated with bone substitute. Eight patients were male and seven female, with relatively equal distribution between both groups. The average bone defect was relatively equal: 14 cc (4-25 cc) for the allograft group and 15.1 cc (4-33 cc) for the ceramic group (P>0.1). During the follow-up, all the lesions gradually disappeared after 12 months, with a time of healing of 18.8 weeks (15-24 weeks) for the allograft group and 20.37 weeks (15-28) for the bone substitute group. There were no significant differences regarding the clinical status and the radiological assessment after 12 months. No patient required extra pain medication after 2 weeks. No complications have been recorded. The surgical treatment of small and medium sized lytic benign tumors has good results with both types of graft that were studied. Using tricalcium phosphate mixed with hydroxyapatite as bone substitute represents a good and low cost alternative, but it is a relatively fragile material with a slower time to integrate compared to the allograft.